PENGARUH DOSIS DAN INTERVAL PUPUK PELENGKAP CAIR TERHADAP DAYA HASIL TANAMAN PADI (Oryza sativa. L) MODEL JAJAR LEGOWO - Luluk Sulistiyo Budi; Sri Rahayu; Ma’ruf Pambudi Nurwantara (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2018)
Food needs in the form of rice in Indonesia are still a large component, the population continues to increase, so efforts to increase rice production can also be done well. The research objective is to produce plants optimally and specific targets needed. The research method used a factorial randomized block design using two factors. The first factor is the POC dose with 4 levels namely 0 cc/ l, 1 cc / l, 1.5 cc / l, and 2cc / l and the second factor is the interval of giving 4 days, 6 days once and 8 times a day. The parameters of the observations included plant height, leaf area, number of tillers, panicle number, panicle length, number of grains, the weight of wet stover, dry weight of stover, the weight of dry paddy grain and weight of dry milled rice. Analisa results using Duncan's double test with a 0.5% royal hose. The results obtained by the combination of POC interval and dose intervals were interaction and gave a significant effect on the rice crop production of the Jowo Legowo model on all observed parameters. The combination of a 4-day time interval with a powerful dose of 1.5 cc/liter of air, although it cannot be used with 2.00cc / liter, with milled dry grain production of 8.96 tons/ha.